2012
DOI: 10.1002/adma.201104461
|View full text |Cite
|
Sign up to set email alerts
|

Block Copolymer as a Nanostructuring Agent for High‐Efficiency and Annealing‐Free Bulk Heterojunction Organic Solar Cells

Abstract: The addition of a block copolymer to the polymer/fullerene blend is a novel approach to the fabrication of organic solar cells. The block copolymer (P3HT-b-P4VP) is used as nanostructuring agent in the active layer. A significant enhancement of the cell efficiency is observed, in correlation with morphology control, both before (as-cast) and after the annealing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 44 publications
1
65
0
Order By: Relevance
“…[8][9][10]13] The tendency of fullerenes to diffuse through the polymer phase resulting in the formation of large fullerene crystals via Ostwald ripening is regarded as the primary cause. Several techniques have been developed over the last decade to improve the thermal stability of polymer:fullerene blends including the use of high glass transition temperature polymers, [14] ternary blends with compatibilizers such as block copolymers, [15][16][17] amorphous fullerene derivatives, [18,19] donor-acceptor systems with enhanced interactions, [20,21] functionalized side chains on the polymer, [22] thermocleavable polymers, [23] light-induced fullerene polymerization, [24,25] and cross-linkable materials. [26,27] Furthermore, it was shown that mixtures of different fullerenes can improve the thermal stability of BHJs.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10]13] The tendency of fullerenes to diffuse through the polymer phase resulting in the formation of large fullerene crystals via Ostwald ripening is regarded as the primary cause. Several techniques have been developed over the last decade to improve the thermal stability of polymer:fullerene blends including the use of high glass transition temperature polymers, [14] ternary blends with compatibilizers such as block copolymers, [15][16][17] amorphous fullerene derivatives, [18,19] donor-acceptor systems with enhanced interactions, [20,21] functionalized side chains on the polymer, [22] thermocleavable polymers, [23] light-induced fullerene polymerization, [24,25] and cross-linkable materials. [26,27] Furthermore, it was shown that mixtures of different fullerenes can improve the thermal stability of BHJs.…”
Section: Introductionmentioning
confidence: 99%
“…With the thermal stability of all-polymer and polymer-fullerene blend microstructures being particularly problematic [19], block copolymers present a potential solution. Indeed, it has been shown that when block copolymers are used as additives in bulk heterojunction donor–acceptor blend layers, the morphology of the resulting ternary blend film can be more stable over long periods of time, even under thermal annealing [14,2021]. …”
Section: Introductionmentioning
confidence: 99%
“…A GISAXS/GIWAXS setup has already been successfully used to study the structure of thin polymeric films (Renaud et al, 2012) and to monitor the structure formation during spin coating. However, in this manuscript we will discuss only experiments using the conventional transmission geometry.…”
Section: Beamline Descriptionmentioning
confidence: 99%